2011
DOI: 10.1053/j.ajkd.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the CKD Epidemiology Collaboration (CKD-EPI) and Modification of Diet in Renal Disease (MDRD) Study Equations: Prevalence of and Risk Factors for Diabetes Mellitus in CKD in the Kidney Early Evaluation Program (KEEP)

Abstract: Background Diabetes is a leading cause of chronic kidney disease (CKD). Whether reclassification of CKD stages based on glomerular filtration rate estimated using the CKD Epidemiology Collaboration (CKD-EPI) equation versus the Modification of Diet in Renal Disease (MDRD) Study equation modifies estimates of prevalent risk factors across stages is unknown. Methods This is a cross-sectional analysis of data from the Kidney Early Evaluation Program (KEEP), a community-based health screening program targeting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
3
21
0
1
Order By: Relevance
“…In line with numerous previously published studies, we showed a higher prevalence of diabetes and insulin resistance in patients with impaired renal function, as diabetes is the most common cause of CKD and its end-stage disease [36,37]. However, the results of multivariate regression analysis did not prove the independent impact of insulin resistance on visfatin/NAMPT concentration variability.…”
Section: Discussionsupporting
confidence: 83%
“…In line with numerous previously published studies, we showed a higher prevalence of diabetes and insulin resistance in patients with impaired renal function, as diabetes is the most common cause of CKD and its end-stage disease [36,37]. However, the results of multivariate regression analysis did not prove the independent impact of insulin resistance on visfatin/NAMPT concentration variability.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of CKD is increasing worldwide [1,2]. Renal interstitial fibrosis is an inevitable result of virtually all progressive kidney diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Jermendy György és mtsai által publikált reprezentatív felmérés [2] szerint Magyarországon a betegség prevalenciája 2010-ben 7,47% volt a 20-69 éves korosztályban. A diabetes mellitus a leggyakoribb oka többek között a végstádiumú veseelégtelen-ségnek, és a krónikus vesebetegség negyedik-ötödik stá-diumában a gyakorisága meghaladhatja az 50%-ot [3].…”
Section: Rövidítésekunclassified